2002
DOI: 10.1017/s0967199402002320
|View full text |Cite
|
Sign up to set email alerts
|

Determination and synchronisation of G1-phase of the cell cycle in 2- and 4-cell mouse embryos

Abstract: Incorporation of [3H]thymidine at different concentrations into mouse embryos at early developmental stages was determined by autoradiography. Methods to synchronise the G1-phase of mouse 2- and 4-cell embryos were also investigated. The results showed that the ability of embryos to incorporate [3H]thymidine increased with development. Embryos at the 4-cell stage were not labelled when the concentration of [3H]thymidine was lower than 5 μCi/ml, whereas the nuclei of embryos at morula and blastocyst stages bega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…One study has demonstrated that high concentration and long-term nocodazole treatment Control indicates the untreated 8-cell embryos; nocodazole indicates the 8-cell embryo treated with nocodazole (0.5 μM) for 12 h; nocodazole-2 indicates 8-cell embryo treated with nocodazole (0.5 μM) for 12 h and then cultured in nocodazole-free KSOM medium for another 30 min resulted in chromosomal abnormality or even embryo-lethal mutants [29]. A 0.05-0.5 μM nocodazole treatment blocked the cell cycle, but it did not damage embryonic development [30]. Therefore, 0.5 μM nocodazole was selected in this study to treat 8-cell mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…One study has demonstrated that high concentration and long-term nocodazole treatment Control indicates the untreated 8-cell embryos; nocodazole indicates the 8-cell embryo treated with nocodazole (0.5 μM) for 12 h; nocodazole-2 indicates 8-cell embryo treated with nocodazole (0.5 μM) for 12 h and then cultured in nocodazole-free KSOM medium for another 30 min resulted in chromosomal abnormality or even embryo-lethal mutants [29]. A 0.05-0.5 μM nocodazole treatment blocked the cell cycle, but it did not damage embryonic development [30]. Therefore, 0.5 μM nocodazole was selected in this study to treat 8-cell mouse embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Each cell, or blastomere, in two-cell embryos contains a complete complement of chromosomes. Disruption of microtubule function during oocyte maturation or fertilization leads to aberrations in embryo chromosomal ploidy (Generoso et al, 1989;Yu et al, 2002;Sun et al, 2005). Although oocyte-derived mRNA and protein products contribute to the first few embryonic divisions, mouse embryos undergoes major zygotic genomic activation (ZGA), during the two-cell stage, to sustain early preimplantation development (Haraguchi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%